Girl code : gaming, going viral, and getting it done - Gonzales, Andrea (Harper, an imprint of HarperCollinsPublishers, 2017)
The authors, who met at a summer computer programming camp for girls, share their knowledge of gaming, programming, and the tech industry, and provide advice on getting into the field of computer programming.